Mexiletine Differentially Restores the Trafficking Defects Caused by Two Brugada Syndrome Mutations - Adrien eMoreau; Dagmar I Keller; Hai eHuang; Véronique eFressart; Christian eSchmied; Quadiri eTimour; Mohamed eChahine (Frontiers Media S.A., 2012)
The human cardiac sodium channel Nav1.5 encoded by the SCN5A gene plays a critical role in cardiac excitability and the propagation of action potentials. Nav1.5 dysfunctions due to mutations cause cardiac diseases such as the LQT3 form of long QT syndrome, conduction disorders, and Brugada syndrome (BrS). They have also recently been associated with dilated cardiomyopathy. BrS is characterized by coved ST segment elevation on surface ECGs and lethal ventricular arrhythmias in an apparently structurally normal heart. Nav1.5 mutations that cause BrS result in a loss of channel function.Our aim was to functionally characterize two novel Nav1.5 mutations (A124D and V1378M) in BrS patients.Wild-type (WT) and mutant Nav1.5 channels were expressed in tsA201 cells in the presence of the β1-auxiliary subunit. The patch-clamp technique and immunocytochemistry approaches were used to study the mutant channels and their cellular localization.The two mutant channels displayed a dramatic reduction in current density but had normal gating properties. The reduction in current density was caused by the retention of channel proteins in the endoplasmic reticulum (ER). Mutant channel retention could be partially reversed by incubating transfected cells at 25°C and by treating them with mexiletine (for A124D but not V1378M), or with curcumin or thapsigargin, two drugs that target ER resident proteins.It is likely that the clinical phenotypes observed in these two BrS patients were related to a surface expression defect caused by ER retention.